2001
DOI: 10.1034/j.1600-0781.2001.170602.x
|View full text |Cite
|
Sign up to set email alerts
|

Total body exposure to ultraviolet radiation does not influence plasma levels of immunoreactive beta-endorphin in man

Abstract: On the basis of these results, the skin does not appear to contribute significantly to the levels of circulating betaE or ACTH. These data offer no support for the hypothesis that exposure to UVR leads to an increased concentration of circulating betaE, which could contribute to the feeling of well-being that often accompanies sun-bathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Twenty-six healthy volunteers were exposed to 15 J/cm² UVA irradiation on a single occasion, but this had no eVect on E level. Repeated irradiation of 35 subjects with UVA and UVB did not inXuence ATCH level either (Wintzen et al 2001). Gambichler et al (2002) published similar observations regarding immunoreactive E and metenkephalin.…”
Section: Phototherapymentioning
confidence: 55%
“…Twenty-six healthy volunteers were exposed to 15 J/cm² UVA irradiation on a single occasion, but this had no eVect on E level. Repeated irradiation of 35 subjects with UVA and UVB did not inXuence ATCH level either (Wintzen et al 2001). Gambichler et al (2002) published similar observations regarding immunoreactive E and metenkephalin.…”
Section: Phototherapymentioning
confidence: 55%
“…68 However, significant increases in plasma opioid levels after tanning have yet to be demonstrated in human subjects. 69,70 Other investigations of the effect of UV light on mood have focused on the photosensitivity of the pineal melatonin-generating system. The enzyme N-acetyltransferase, which initiates the conversion of serotonin to melatonin, is reported to be inhibited by UVA radiation.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier studies found increased levels of endorphins following UVL exposure, 14,15 subsequent studies have not confirmed these findings. 16,17 Another investigative approach to the endorphin theory of tanning behavior would be to evaluate positron emission tomography brain images of subjects identified by mCAGE and mDSM-IV-TR as possibly having an SRD with respect to UVL tanning. Comparisons of observations following control (sham) vs actual exposure to UVL would be analogous to research approaches used to study other human addictions.…”
Section: Commentmentioning
confidence: 99%